2018
DOI: 10.14238/pi58.2.2018.66-70
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis risk factors in children with smear-positive tuberculosis adult as household contact

Abstract: Background Children in household contact of adults with smear-positive tuberculosis (TB) are at higher risk of TB infection. Screening of these children is a main strategy for eliminating childhood TB.Objective To determine risk factors of TB among children in household contact with smear-positive adult TB patients.Methods This case-control study was conducted in 5 public health centers at Batu Bara District, North Sumatera. We studied children from birth to 18 year-old living in the same house as adults with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…(15) This findings is consistent with previous studies that have demonstrated an association between having contact history with TB cases and the incidence of TB. (8,9,11,12,14,16) Malnutrition was another risk factor of TB infection. (2,(16)(17)(18) The association between malnutrition and TB incidence is bi-directional.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(15) This findings is consistent with previous studies that have demonstrated an association between having contact history with TB cases and the incidence of TB. (8,9,11,12,14,16) Malnutrition was another risk factor of TB infection. (2,(16)(17)(18) The association between malnutrition and TB incidence is bi-directional.…”
Section: Discussionmentioning
confidence: 99%
“…(8,9,11,12,14,16) Malnutrition was another risk factor of TB infection. (2,(16)(17)(18) The association between malnutrition and TB incidence is bi-directional. TB predisposes the patient to malnutrition and malnutrition increases the vulnerability of developing the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Populasi padat menyebabkan interaksi yang intens dan durasi berkontak dengan penderita tuberkulosis semakin tinggi sehingga berpengaruh terhadan persebaran Mycobacterium tuberkulosis (Martinez et al, 2020;Donald et al, 2010). Hasil penelitian Hajarsyah dkk menyatakan bahwa, faktor risiko yang paling berpengaruh terhadap kejadian tuberkulosis pada anak-anak selain durasi kontak dengan penderita adalah status gizi, lalu diikuti status imunisasi, jumlah orang yang tinggal dalam satu rumah, dan kebiasaan tidur dalam satu ranjang (Hajarsyah et al, 2018).…”
Section: Pembahasanunclassified